Germanophobia in Switzerland - Marc Helbling (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
This paper considers two common assumptions that often arise in the empirical literature on xenophobia—namely that xenophobic attitudes are found mostly among the poorly educated, and that xenophbia mainly concerns immigrants from low social classes and from geographically and culturally disparate nations. These arguments will be discussed in the context of the migration of high-skilled Germans to Switzerland, a phenomenon that has increased markedly in the last few years, leading to major controversies. A survey conducted in the city of Zurich has shown that Germans are considered less likable than other Western Europeans. Over the course of my analyses, two arguments are tested. First, I consider whether the boundaries between culturally similar groups are actually less fragile than those occurring between more dissimilar groups. Following this line of reasoning, we consider whether Swiss-Germans' popularly evoked “inferiority complex” towards Germans might lead Swiss-Germans to perceive German immigration as a cultural threat. Second, I consider whether well-educated people in high positions may feel threatened by new arrivals who are similarly welleducated. This rationale corresponds to the classic argument that working class people are xenophobic out of a fear that immigrants will take their jobs. Ultimately, this study finds empirical support for both arguments. – – Das Paper hinterfragt zwei in der Forschungsliteratur zu Fremdenfeindlichkeit gängige Annahmen und Befunde, die besagen, dass fremdenfeindliche Einstellungen vor allem unter gering gebildeten Angehörigen der Mehrheitsgesellschaft zu finden seien und sich in der Regel gegen Migranten aus unteren sozialen Schichten und aus geographisch wie kulturell fernen Ländern richten würden. Überprüft werden diese Annahmen im Kontext der deutschen Einwan-derung in die Schweiz, die in den letzten Jahren stark angestiegen ist und spür-bare Kontroversen ausgelöst hat. Eine in der Stadt Zürich durchgeführte Umfrage hat ergeben, dass Deutsche im Vergleich zu anderen Westeuropäern als weniger sympathisch angesehen werden. Zwei Argumentationen werden untersucht: Zum einen wird die Hypothese überprüft, dass Grenzen zwischen Gruppen, die sich kulturell sehr nahe stehen, nicht notwendigerweise leichter zu überwinden sein müssen. Der mitunter angeführte Minderwertigkeitskomplex der Deutsch- Schweizer gegenüber Deutschen könnte dazu führen, dass die deutsche Einwanderung als kulturelle Bedrohung empfunden wird. Zum anderen ist es auch möglich, dass sich Bessergebildete in höheren beruflichen Positionen durch vergleichbar gut gebildete Zuwanderer durchaus bedroht fühlen. Diese Hypothese entspricht dem klassischen Argument, dass Angehörige der Arbeiterklasse deswegen fremdenfeindlich sind, weil sie befürchten, ihre Jobs an Immigranten zu verlieren. Beide Hypothesen werden in dieser Studie empirisch belegt.
Keywords: 330; Education; German migration; realistic individual threat; symbolic group threat; Switzerland; xenophobia